GENERAL RULES OF CRIMINAL SENTENCING - Elena Anatolievna Ivanchenko (Вестник Северо-Кавказского федерального университета)
The article is devoted to the general rules of criminal sentencing, as well as discussion on the use of the institution of criminal law. The paper emphasizes that the criminal punishment – a complex institution of criminal law, which is a system of criminal-legal categories, with the help of which the relationship between the concepts of «crime» and «punishment». It is a socially dangerous act prohibited by the criminal law, and is the only condition for the existence and application of penalties.